GAMBARAN ASUPAN ZAT GIZI MAKRO DAN STATUS GIZI MAHASISWA POLTEKKES KEMENKES SORONG PADA MASA PANDEMI COVID 19 - Swietienia Daniela Fatie; Anjar Briliannita; Wilma Florensia (Nursing Arts, 2021)
ABSTRACTTeenagers as the next generation need to get the right nutrients because it important role in nutritional status, providing energy for the body and regulating metabolic processes in the body, accelerating growth and improving tissue systems in the body and improving tissue systems in the body. The purpose of this study was to describe the intake of macronutrients of students of the DIII Nutrition Study Program at the Health Polytechnic of the Ministry of Health, Sorong during the Covid 19 pandemic. This type of research was descriptive using a cross sectional design. The level of macronutrient intake was assessed using 24-hour Food Recall for 1 week, while the measurement of the nutritional status of respondents was measured based on anthropometric measurements (BMI). The number of respondents is 46 people who meet the inclusion criteria. The results obtained in this study, namely the nutritional status of the highest respondent with good nutritional status (50%), the lowest nutritional status withobesity (8.6%) and poor nutritional status (30.4%). Meanwhile, the average respondent's energy intake is less (86.10%), the respondent's protein intake is on average less (63.4%), the respondent's fat intake is on average less (78.7%) and the respondent's carbohydrate intake is on average. less average (95.6%). During the COVID-19 pandemic from 2020 to 2021, theaverage student has a good nutritional status. However, the average intake of energy, carbohydrates, protein and fat is still lacking.